On the question of typology of Armenian language - Khachatrian , Lalik (Bulletin of Yerevan University B: Philology, 2022)
In the linguistic literature, different stages of the development of Armenian language (Old Armenian and Modern) from a typological point of view were traditionally characterized by features that, from the point of view of today's methodology, need to be revised, based on the principle of the relationship between the plan of expression and the plan of the content of word forms. Based on the analysis of the nature of the linguistic means of expressing grammatical meanings and the frequency of their use, Old Armenian is typologically the language of the agglutinative system in combination with inflection, and Modern Armenian is the language of the agglutinative system in combination with the analytic-affix type. Such a conclusion gives grounds for revising a number of provisions concerning the classification of the grammatical structure of Armenian language.
Keywords: Old Armenian; Modern Armenian; morphological type; typological characteristic; affixation; inflexion; analytical type; cyntetic type; analytical- affixional type